2004
DOI: 10.1162/003465304323023886
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationarities in Financial Time Series, the Long-Range Dependence, and the IGARCH Effects

Abstract: We give the theoretical basis of a possible explanation for two stylized facts observed in long log-return series: the long-range dependence (LRD) in volatility and the integrated GARCH (IGARCH). Both these effects can be explained theoretically if one assumes that the data are nonstationary. © 2004 President and Fellows of Harvard College and the Massachusetts Institute of Technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
335
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 507 publications
(345 citation statements)
references
References 17 publications
9
335
0
1
Order By: Relevance
“…Recently, it has been suggested that either long memory (Mikosch and Starica, 2004) or parameter changes (Hillebrand, 2005) in the data generating process can give the impression of IGARCH model. …”
Section: The Integrated Garch Modelsmentioning
confidence: 99%
“…Recently, it has been suggested that either long memory (Mikosch and Starica, 2004) or parameter changes (Hillebrand, 2005) in the data generating process can give the impression of IGARCH model. …”
Section: The Integrated Garch Modelsmentioning
confidence: 99%
“…Second, they argue that observed IGARCH behavior may result from misspecification of the conditional variance function. For example, a two components structure or ignored structural breaks in the unconditional variance ( [58] and [70]) can result in IGARCH behavior. Table 9 gives Lo's modified R/S statistic (20) applied to r 2 t and |r t | for Microsoft and the S&P 500.…”
Section: Integrated Garch Modelmentioning
confidence: 99%
“…Including dummy variables to account for such shifts diminishes the degree of GARCH persistence. More recently, Mikosch and Stărică (2004) prove that the IGARCH model makes sense when non-stationary data reflect changes in the unconditional variance. Hillebrand (2005) shows that in the presence of neglected parameter change-points, even a single deterministic change-point can cause GARCH to measure volatility persistence inappropriately.…”
Section: Introductionmentioning
confidence: 99%